UNCOVERING TRANSPARENCY IN BIODIVERSITY ACCOUNTING STANDARDS IN INDONESIA’S MINING SECTOR: English - Simon Nisja Putra Zai; Yuni Pristiwati Noer Widianingsih (Accounting Profession Journal (APAJI), 2025)
This study examines the transparency of biodiversity reporting by mining companies in Indonesia based on the Global Reporting Initiative (GRI) guidelines. Using a qualitative approach, this study analyzed 60 sustainability reports from 30 mining companies listed on the Indonesia Stock Exchange (IDX) in the 2022-2023 periods. The results showed that the level of biodiversity reporting was still low, where out of 30 GRI indicators; only 11 indicators (36.67%) were reported. These results show that the company is more focused on short-term operational and reputational issues than long-term strategic efforts.